An Analysis of Capital Control and Long Memory Effects in Bursa Malaysia Stock Exchange - Feng, Weishan (2006)
On 1 September 1998, the Malaysian government imposed capital control to recover its economy from Asian financial crisis. This study examined the effect of capital control on Bursa Malaysia Main Board indices. It found the indices reacted quickly to reflect the effect of capital control announcement. The ARFIMA (p, d, q) model then was employed to examine the long memory effects in all indices during five different periods. It is found that long memory existed in Consumer Products Index, and Tin and Mining Index during the pre-capital control period. Long memory effect was found in KLCI, Construction Index, EMAS Index, Finance Index, and Trade and Service Index over the post-capital control period (including capital control year). Plantation Index and Properties Index had long memory effect over both entire period and pre-capital control period. While no long memory effect was found in Industrial Index over all periods, the Industrial Products Index exhibited long memory in post-capital control periods (both excluding and including the capital control year).By using the ARFIMA-GARCH ( 1, 1 ) model, it was found that long memory existed in Plantations Index and Properties Index during the pre-capital control period. In post-capital control period (including capital control year), it was found long memory existed in KLCI Construction , Index, EMAS Finance , Index, and Industrial Products Index. Over the entire period, only Plantations Index and Properties Index still can be foundlong memory byARFIMA-GARCH ( 1, 1 ) model.